Comparison of biofilm models for producing artificial active white spot lesions - Erika Michele dos Santos ARAUJO; Cristina de Mattos Pimenta VIDAL; Min ZHU; Jeffrey A. BANAS; Anderson Zanardi de FREITAS; Niklaus Ursus WETTER; Adriana Bona MATOS (University of São Paulo, 2024)
Abstract Creating artificial caries-like lesions that mimic the complex changes observed in natural caries is essential for properly evaluating new strategies, dental materials, and devices designed to arrest their progression and avoid more costly and invasive treatments. Objective This study compared three protocols for developing artificial white spot lesions (WSL) using biofilm models. Methodology In total, 45 human enamel specimens were sterilized and allocated into three groups based on the biofilm model: Streptococcus sobrinus and Lactobacillus casei (Ss+Lc), Streptococcus sobrinus (Ss), or Streptococcus mutans (Sm). Specimens were incubated in filter-sterilized human saliva to form the acquired pellicle and then subjected to the biofilm challenge consisting of three days of incubation with bacteria (for demineralization) and one day of remineralization, which was performed once for Ss+Lc (four days total), four times for Ss (16 days total), and three times for Sm (12 days total). After WSL creation, the lesion fluorescence, depth, and chemical composition were assessed using Quantitative Light-induced Fluorescence (QLF), Polarized Light Microscopy (PLM), and Raman Spectroscopy, respectively. Statistical analysis consisted of two-way ANOVA followed by Tukey's post hoc test (α=0.05). WSL created using the Ss+Lc protocol presented statistically significant higher fluorescence loss (ΔF) and integrated fluorescence (ΔQ) in comparison to the other two protocols (p<0.001). Results In addition, Ss+Lc resulted in significantly deeper WSL (137.5 µm), followed by Ss (84.1 µm) and Sm (54.9 µm) (p<0.001). While high mineral content was observed in sound enamel surrounding the WSL, lesions created with the Ss+Lc protocol showed the highest demineralization level and changes in the mineral content among the three protocols. Conclusion The biofilm model using S. sobrinus and L. casei for four days was the most appropriate and simplified protocol for developing artificial active WSL with lower fluorescence, higher demineralization, and greater depth.